Modeling of Partial Discharge Activity in Spherical Cavities Within a Dielectric Material - Illias, Hazlee Azil; Chen, G.; Lewin, P. (Institute of Electrical and Electronics Engineers, 2011)
The partial discharge (PD) activity in a cavity within a solid dielectric insulation material is known to be dependent on the size, shape, and location of the cavity. These factors have a strong influence on the local electric field distribution, which directly affects PD activity and its characteristic behavior. In this work, a model for a spherical cavity within a homogeneous dielectric material was developed using finite element analysis (FEA) software. The model was used to study the influence of different cavity conditions on local electric field distribution and consequent PD activity. The study involved variation of cavity diameter and cavity location within the dielectric material. In addition, experimental measurements were undertaken using epoxy samples containing single spherical cavities of different diameters. The results verify that PD activity is influenced by the size of the cavity within the dielectric material, and the results will enable users to evaluate key PD parameters that are directly related to the electric field distribution and the physical properties of the cavity. These parameters include the PD repetition rate, maximum PD charge amplitude, and the PD inception voltage level. This study, involving comparison of experimental and simulation data, may therefore give insight into measured PD characteristics.